Estrogen receptors, ERK1/2 phosphorylation and reactive oxidizing species in red blood cells from patients with rheumatoid arthritis - Di Franco, Manuela; Vona, Rosa; Gambardella, Lucrezia; Cittadini, Camilla; Favretti, Martina; Gioia, Chiara; Straface, Elisabetta; Pietraforte, Donatella (Frontiers in Physiology, 2022)
Red blood cells (RBCs) are recognized to be important pathogenetic determinants in several human cardiovascular diseases (CVD). Undergoing to functional alterations when submitted to risk factors, RBCs modify their own intracellular signaling and the redox balance, shift their status from antioxidant defense to pro-oxidant agents, become a potent atherogenic stimulus playing a key role in the dysregulation of the vascular homeostasis favoring the developing and progression of CVD. Rheumatoid arthritis (RA) is a chronic autoimmune disease associated with a significantly increased risk of cardiovascular mortality with a prevalence from 2 to 5 more likely in woman, mainly attributed to accelerated atherosclerosis. The purpose of this study was to correlate the RA disease activity and the RBCs functional characteristics. Thirty-two women (aged more than 18 years) with RA, and 25 age-matched healthy women were included in this study. The disease activity, measured as the number of swollen and painful joints (DAS-28), was correlated with i) the expression of RBCs estrogen receptors, which modulate the RBC intracellular signaling, ii) the activation of the estrogen-linked kinase ERK½, which is a key regulator of RBC adhesion and survival, and iii) the levels of inflammatory- and oxidative stress-related biomarkers, such as the acute-phase reactants, the antioxidant capacity of plasma, the reactive oxidizing species formation and 3-nitrotyrosine. All the biomarkers were evaluated in RA patients at baseline and six months after treatment with disease-modifying anti‐rheumatic drugs (DMARDs). We found, for the first times, that in RA patients i) the DAS-28 correlated with RBC ER-α expression, and did not correlate with total antioxidant capacity of plasma; ii) the RBC ER-α expression correlated with systemic inflammatory biomarkers and oxidative stress parameters, as well as ERK½ phosphorylation; and iii) the DMARDs treatments improved the clinical condition measured by DAS-28 score decrease, although the RBCs appeared to be more prone to pro-oxidant status associated to the expression of survival molecules. These findings represent an important advance in the study of RA determinants favoring the developing of CVD, because strongly suggest that RBCs could also participate in the vascular homeostasis through fine modulation of an intracellular signal linked to the ER-α